Stop Release in Polish English — Implications for Prosodic Constituency - Schwartz, Geoffrey; Balas, Anna; Rojczyk, Arkadiusz (Research in Language, 2014)
Although there is little consensus on the relevance of non-contrastive allophonic processes in L2 speech acquisition, EFL pronunciation textbooks cover the suppression of stop release in coda position. The tendency for held stops in English is in stark opposition to a number of other languages, including Polish, in which plosive release is obligatory. This paper presents phonetic data on the acquisition of English unreleased stops by Polish learners. Results show that in addition to showing a tendency for the target language pattern of unreleased plosives, advanced learners may acquire more native-like VC formant transitions. From the functional perspective, languages with unreleased stops may be expected to have robust formant patterns on the final portion of the preceding vowel, which allow listeners to identify the final consonant when it lacks an audible release burst (see e.g. Wright 2004). From the perspective of syllabic positions, it may be said that ‘coda’ stops are obligatorily released in Polish, yet may be unreleased in English. Thus, the traditional term ‘coda’ is insufficient to describe the prosodic properties of post-vocalic stops in Polish and English. These differences may be captured in the Onset Prominence framework (Schwartz 2013). In languages with unreleased stops, the mechanism of submersion places post-vocalic stops at the bottom of the representational hierarchy where they may be subject to weakening. Submersion produces larger prosodic constituents and thus has phonological consequences beyond 'coda' behavior.